STATUS GIZI DENGAN PERKEMBANGAN ANAK USIA TODDLER - Lilis Maghfuroh (Universitas Nahdlatul Ulama Surabaya, 2018)
In general, the process of each child's developmental stages is the same, that is the result of the maturation process. But in accomplishment, every child has a different speed. Based on the initial survey 5 (50%) children doubt in the development. The purpose of this study was to determine the relationship among nutritional status with the development of children age toddler. This research design using correlation analytical method with Cross Sectional approach. The number of 45 samples of children under five with simple random sampling technique with the independent variable of nutritional status and the dependent variable of development, analysis using Spearmen test with ρ <0.05. The test results obtained significant 0.002 (ρ <0.05). Shows there is a relationship of nutritional status with the development of children age toddler. Mother's efforts to improve the development of toddler age children by improving nutritional status that includes 4 healthy 5 perfect in accordance with the needs of children aged toddler and provides stimulation of development through the provision of educational games and immediately bring the child to health personnel if there is suspected deviation of development